Performance of Imaging Techniques in Non-invasive Diagnosis of Non-alcoholic Fatty Liver Disease in Children: A Systematic Review and Meta-Analysis - Yu, Qun; Liu, Yiwei; Hu, Peipei; Gao, Feng; Huang, Guoqing (Frontiers in Pediatrics, 2022)
Abstract Background and Aim: Nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in children. With the continuous emergence of various noninvasive diagnostic methods, imaging technology has always been considered as a potential alternative to liver biopsy. This study aimed to evaluate the diagnostic performance of a new imaging technology in children with NAFLD so as to search for the most potential imaging technology. Methods：We searched English and Chinese databases. English databases included Cochran library, Embase, PubMed, and Web of Science, while Chinese databases included Wanfang database and China National Knowledge Internet. Results: Finally, 11 articles were included (12 studies,one of which included studies on both fibrosis and steatosis). Further, 26.2% of patients had mild steatosis, 34.1% had moderate steatosis, and 34.9% had severe steatosis. Also, 64.0% had mild fibrosis, 29.1% had significant fibrosis, 13.8% had advanced fibrosis, and 2.8% had liver cirrhosis. The summary sensitivity and specificity of elastography in diagnosing fibrosis were 86% [95% confidence interval (CI), 67–95] and 93% (95% CI, 87–96), respectively, and area under the receiver operating characteristic curve (AUROC)0.96 (95% CI, 94–97); transient elastography (TE) showed very good sensitivity and specificity: 98% (95% CI, 92–100) and 97% (95% CI, 93–99), respectively. Irrespective of the stage of fibrosis diagnosis, TE also showed high sensitivity (97%–100%). The overall sensitivity and specificity of imaging technology in diagnosing steatosis were 89% (95% CI, 71–96) and 89% (95% CI, 72–96), and AUROC 0.95 (95% CI, 93–97).Multifrequency magnetic resonance elastographyhepatic fat fraction (mMRE-HFF) had the highest sensitivity (87%, 95% CI 77–97). Conclusions: Imaging technology has a good diagnostic performance for children with NAFLD, especially the diagnosis of liver fibrosis in children with NAFLD based on ultrasound and MRI elastography. Compared with different imaging techniques, TE has the best performance in children with significant fibrosis diagnosed with NAFLD. Liver stiffness measurement (LSM)is expected to become a biological indicator for routine screening, dynamic monitoring of disease changes, and prognostic evaluation.